High frequency of asymptomatic hyperparathyroidism in patients with fibromyalgia: random association or misdiagnosis? - Juliana Maria de Freitas Trindade Costa (Revista Brasileira de Reumatologia)
ABSTRACT Fibromyalgia (FM) and hyperparathyroidism may present similar symptoms (musculoskeletal pain, cognitive disorders, insomnia, depression and anxiety), causing diagnostic confusion. Objectives: To determine the frequency of asymptomatic hyperparathyroidism in a sample of patients with FM and to evaluate the association of laboratory abnormalities to clinical symptoms. Methods: Cross-sectional study with 100 women with FM and 57 healthy women (comparison group). Parathyroid hormone (PTH), calcium and albumin levels were accessed, as well as symptoms in the FM group. Results: In FM group, mean serum calcium (9.6 ± 0.98 mg/dL) and PTH (57.06 ± 68.98 pg/mL) values were considered normal, although PTH levels had been significantly higher than in the comparison group (37.12 ± 19.02 pg/mL; p = 0.001). Hypercalcemic hyperparathyroidism was diagnosed in 6% of patients with FM, and 17% of these women exhibited only high levels of PTH, featuring a normocalcemic hyperparathyroidism, with higher frequencies than those expected for their age. There was no significant association between hyperparathyroidism and FM symptoms, except for epigastric pain, which was more frequent in the group of patients concomitantly with both diseases (p = 0.012). Conclusions: A high frequency of hyperparathyroidism was noted in women with FM versus the general population. Normocalcemic hyperparathyroidism was also more frequent in patients with FM. Longitudinal studies with greater number of patients are needed to assess whether this is an association by chance only, if the increased serum levels of PTH are part of FM pathophysiology, or even if these would not be cases of FM, but of hyperparathyroidism.